Association between sugary beverage and unhealthy food consumption and stunting among children under five - Maharani Permata Sari; Yusrawati Yusrawati; Afdal Afdal; Desmawati Desmawati; Arni Amir; Finny Fitry Yani (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Stunting is a condition of growth failure in children under five caused by chronic malnutrition, resulting in children being too short for their age. Malnutrition occurs during the first one thousand (1000) days of life, starting from conception until the child reaches two years of age; however, the condition of stunting becomes visible after the child was two years old. The risk factors contributing to stunting are consumption of sweetendebeverage and unhealthy foods, such as snacks high in sugar, salt, and fat, as well as sweetened and carbonated drinks that are low in nutrients. Such dietary patterns can lead to an imbalance in the intake of macro- and micronutrients that play an important role in a child’s growth. Purpose: To analyze the relationship between the consumption of unhealthy foods and beverages and the incidence of stunting. Method: This study was an analytic observational with a retrospective case control design. The sample in this study were mothers who had toddlers aged 24-48 months with case and control groups. The total sample in this study was 138 with an unpaired categorical comparative formula. The sampling method in the case group was directly carried out by consecutive sampling, while in the control group it was carried out by proportional sampling first and then taken by consecutive sampling. Results: The results of this study show that there were no relationship between the consumption of sweetened beverage (p = 0.232) and the consumption of unhealthy foods (p = 0.086) with the incidence of stunting in the working area of Pagambiran Public Health Center, Padang City (p-value < 0.05). Conslusion: The conclusion of this study are that there are no relationship between the consumption of sweetened beverage consumption and the incidence of stunting in the working area of Pagambiran Public Health Center, as well as no relationship between the consumption of unhealthy foods and the incidence of stunting in the same area